Precedent Units as a Means of Suggestion Realization in the Ukrainian Media Discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is devoted to the studying of the suggestive potential of precedent units in the Ukrainian media discourse. There were determined the basic properties of the media discourse. Author characterized the gist of the suggestion as a means of implicit manipulative influence. There were distinguished the precedent phenomena (texts, situations, personalities) and the precedent units (names, expressions). There were revealed the language levels and ways of suggestion realization by the means of precedent units.
Keywords: manipulation; media discourse; precedent phenomenon; precedent unit; suggestion